Ethics, exegesis, and philosophy : interpretation after Levinas - Cohen, Richard A., 1950- (Cambridge University Press, 2001)
This book expands upon Emmanuel Levinas' work to explore his use of 'ethical exegesis', opening up broader questions of interpretation in ethical thinking. Levinas' views of philosophy are considered in contrast to alternative contemporary approaches, such as those found in modern science, psychology, Nietzsche, Freud, Husserl, Heidegger, Sartre and Derrida.